Obligate and facultative slave-making ants: raiding behavior, host-parasite coevolution, and the evolution of slave-making behavior - Bono, Jeremy M., author; Antolin, Michael F., advisor; Hufbauer, Ruth, committee member; Moore, Janice, committee member; Herbers, Joan M., committee member (Colorado State University. Libraries, 2004)
Slave-making ants are social parasites that exploit the labor of workers from a closely related host species by incorporating them into the slave-maker colony as slaves. The unique life-history of slave-making ants makes them suitable for studying a variety of questions ranging from host-parasite coevolution to the evolution of sex allocation strategies. My research focuses on filling two major gaps in our understanding of slave-making ant systems. First, although factors contributing to the evolution of slave-making behavior have been considered for well over a century, the process remains poorly understood. The social and colonial structure of ancestral populations of slave-makers and their hosts is undoubtedly relevant, but we lack information on these traits for a number of slave-making ants and their hosts. Here, I report on the social and colonial structure of an obligate slave-making ant, Polyergus breviceps and two sympatric hosts, Formica subsericea and F. near argentea. My research also moves toward a better understanding coevolution between slave-making ants and their hosts in complex systems that include multiple slave-makers and multiple hosts. My study system includes two hosts, F. subsericea and F. near argentea, which are parasitized by the obligate slave-makers P. breviceps and two facultative slavemakers, F. puberula and F. gynocrates. Here, I compare slave-raiding behavior of the & slave-makers and characterize interactions between slave-makers and hosts that have significance for coevolution.
Keywords: ecology; entomology